2019
DOI: 10.1002/hed.25519
|View full text |Cite
|
Sign up to set email alerts
|

Department of Veterans Affairs Consensus: Preradiation dental treatment guidelines for patients with head and neck cancer

Abstract: Few protocols have been published for the dental management of patients with head and neck cancer to prevent complications from head and neck radiation therapy. Radiation therapy not only affects the tumor cells targeted, but also the dentition, bone, salivary gland, and oral soft tissue structures. A comprehensive dental evaluation prior to head and neck radiation therapy can help prevent many complications. The following clinical guidelines were established by a workgroup of oral health providers within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Any discomfort or trauma to the mouth should be addressed and avoided. 10 When there are time constraints for a complete dental evaluation and treatment protocol in case of intensive chemotherapy, partial dental evaluation and treatment protocols with minor caries, asymptomatic third molars or asymptomatic teeth without excessive probing with depth >8 mm, mobility I or II, or periapical lesions of 5 mm are a viable option. In post-head and neck radiation patients who are compliant fluoride users, the use of chlorhexidine, fluoride mouth rinses, composite resin, resinmodified glass ionomer cement, and amalgam restorations over traditional glass ionomer cement is suggested.…”
Section: Dental Care Protocols In Cancer Patientsmentioning
confidence: 99%
“…Any discomfort or trauma to the mouth should be addressed and avoided. 10 When there are time constraints for a complete dental evaluation and treatment protocol in case of intensive chemotherapy, partial dental evaluation and treatment protocols with minor caries, asymptomatic third molars or asymptomatic teeth without excessive probing with depth >8 mm, mobility I or II, or periapical lesions of 5 mm are a viable option. In post-head and neck radiation patients who are compliant fluoride users, the use of chlorhexidine, fluoride mouth rinses, composite resin, resinmodified glass ionomer cement, and amalgam restorations over traditional glass ionomer cement is suggested.…”
Section: Dental Care Protocols In Cancer Patientsmentioning
confidence: 99%
“…The dental surgeon must diagnose and treat the RT acute oral toxicities 24 (OM [25][26][27] , dysgeusia, 12,22,28,29 infections, pain, and xerostomia) (Table 3), that implicate an inability to eat, speak, clean, increased costs with hospitalization, and reduced quality of life. [30][31][32][33] Nutritional care, constant water intake, and use of salivary substitutes are recommended 12,93 In a recent study, the use of zinc-L-carnosine demonstrated encouraging results in the treatment of dysgeusia in these patients 94…”
Section: Prosthetic Treatmentmentioning
confidence: 99%
“…The dental surgeon must diagnose and treat the RT acute oral toxicities 24 (OM [25][26][27] , dysgeusia, 12,22,28,29 infections, pain, and xerostomia) (Table 3), that implicate an inability to eat, speak, clean, increased costs with hospitalization, and reduced quality of life. [30][31][32][33] Nutritional care, constant water intake, and use of salivary substitutes are recommended 12,93 In a recent study, the use of zinc-L-carnosine demonstrated encouraging results in the treatment of dysgeusia in these patients 94…”
Section: Prosthetic Treatmentmentioning
confidence: 99%